Urban expansion, regeneration and socioenvironmental vulnerability in a mangrove ecosystem at the southeast coastal of São Paulo, Brazil - Moschetto, F. A. [UNESP]; Ribeiro, R. B.; De Freitas, D. M. [UNESP] (Elsevier, 2021)
Uncontrolled expansion of urban areas over mangrove systems is a historical threat for conservation and restoration of coastal landscapes. In Brazil, a country that presents one of the largest mangrove areas on the planet, recent political changes considered mangroves as “Permanent Preservation Areas” with the environmental function of preserving their ecosystem services. Under this regulation, mangrove deforestation is allowed in cases of regularization of irregular occupations and consolidated urban areas. However, these political changes may not be an effective to prevent mangrove deforestation in the country. This study aimed to analyze mangrove deforestation over twenty years in Santos and São Vicente estuarine region located at the Baixada Santista region (southeastern of Brazil), a highly vulnerable region subject to intense land use pressure by urban occupation and activities of the largest port of Latin America. Using remote sensing spatial analysis techniques, we analyzed if changes in Brazilian legislation has been reflected in degradation of mangrove forests over a period of twenty years due to the presence of vulnerable mangroves and accelerate land use pressure by urban occupation and activities of the largest port of Latin America. Findings show that, approximately 10.6 km2 of mangroves in this region have been lost mainly due to irregular low-income occupation processes. The greatest gross loss occurred between the years 1999 and 2011 (8.1 km2). Land regularization has caused mangrove reduction of only 0.03 km2 in 2014, but it is possible that, in this case, mangrove forests were replaced by distinct vegetation physiognomy altering the original vegetation pattern. Demand for mangrove legislation that considers both social adaptation and legal protection has grown to support socioenvironmental vulnerability assessments. The data of this study can support environmental policy in a country that presents one of the largest mangrove areas on the planet.
Keywords: Land use pressure; Low-income settlements; Mangrove deforestation; Remote sensing; Santos and são vicente estuary